Bibliometric Analysis of Social Protection Programs in Social Welfare - Judijanto, Loso; Muhtadi, Muhamad Ammar; Eka Arini, Rani (Westscience Press, 2024)
This bibliometric analysis examines the scholarly discourse surrounding social protection programs in the domain of social welfare. With a focus on understanding the landscape, dynamics, and impact of these initiatives, the study employs systematic methodologies to analyze a comprehensive body of literature spanning disciplines such as economics, sociology, public policy, and development studies. Through citation metrics, top-cited research articles, and network visualizations, the study illuminates key thematic clusters, temporal shifts in research focus, and potential future research directions. The findings underscore the enduring relevance and influence of social protection research, offering valuable insights for academia, policy formulation, and program implementation in enhancing societal well-being and fostering inclusive development.